Pengembangan Media Pembelajaran Video Animasi Menggunakan Software Powtoon Pada Materi SPLDV - Garsinia, Dika; Kusumawati, Ratih; Wahyuni, Arie (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika (JRPIPM), 2020)
This research uses quantitative descriptive methods. The subjects of this study were 28 students of class VIII Al Bisyri Islamic Middle School. Data obtained by observation, questionnaire, and written test. ADDIE development model (Analysis, design, development, implementation, and evaluation). Data collection instruments used in the form of learning media questionnaires, student response questionnaires, rational test results. From the results of the research process obtained the value of media experts with an average score of 87.08 (good category), while the mathematics teacher material experts obtained an average score of 88.57 (very good category) so that the media included in the valid category. From the results of the practicality of Powtoon animation video learning media obtained an average score of 84.96 (practical categories), so that it meets the practical aspects in terms of effective, interactive, interesting, efficient, and creative. Whereas based on the posttest value which is higher than the pretest value, the posttest value is 81.50 higher than the pretest value of 67.57 that the effective learning media is used. Based on this analysis it can be concluded that the video animation media using Powtoon software has fulfilled valid, practical and effective criteria.